Using a blue landscape to mitigate heat stress during a heatwave event: a simulation study in a hot-humid urban environment. Issue 3 (10th March 2023) - Zeeshan, Muhammad; Ali, Zaib
Abstract: The urban heat island (UHI) phenomenon and climate change have become the major concerns for city sustainability in the wake of global warming and rapid growth in urbanization. This has resulted in increased intensity of heat stress and worsened outdoor thermal environmental conditions in urban microclimates. Water bodies are among the most effective means to alleviate the UHI and improve the thermal environment of urban microclimates. The thermal comfort conditions are observed at the pedestrian's level in a horizontal direction and at different vertical levels by assessing the reduction in three variables: ambient air temperature, surface temperatures, and alteration of flow velocity. The water body model used in this simulation is first validated using the sub-configuration method by replicating a previous experimental study. Two different scenarios (one with a realistic setting and the other with a representative water body) were studied and the results show that, for isolated streets, the water bodies can effectively improve thermal comfort conditions by reducing ambient air temperature (i.e. a reduction of 0.9 °C) and surface temperature by 3.5 °C, thereby reducing energy consumption. Moreover, a significant increase in wind velocity was also observed reaching its maximum value at peak times of thermal stress. HIGHLIGHTS: Climate change adaptation through the blue landscape in real urban areas: evaluation through predicting its thermal performance under hot, humid climatic conditions, not only at the pedestrian's height but also at diverse vertical levels. Water bodies can effectively improve thermal comfort conditions by reducing air temperature. Urban water bodies cause a significant increase in wind velocity, thus improving ventilation.